O estatuto da subjetividade do doente na semiótica médica germânica na virada do século XIX - Solon, Luiz Ricardo (2016)
Starting in the 1750s, Germany served as stage for a strong debate on medical semiotics aiming at integrating the signs and symptoms exhibited by patients with the pathophysiology of disease and therapeutic indications. By the same time, a movement emphasizing the value of the verbal sign emerged within the scope of literary criticism based on the ancient notion of mimesis, i.e., ut pictura poesis. This new approach deeply impregnated the contemporary medical debate until the first decades of the 19th century, resulting in the polar positions: one, known as pragmatic or diagnostic semiotics, prioritized the signs that revealed disease, while the other, advocated by S. Hahnemann, the founder of homeopathy, considered practically the signs representing the subjective symptoms of the patient only. One among the conceptual elements that distinguished between both approaches was the role attributed to the doctor, as either servant or minister of the healing power of nature, which led clinical investigation to the notions of individual disease and internal truth